Atividade antimicrobiana sobre fitopatógenos: chalconas metoxiladas e óleos essenciais de Lippia gracilis e seus compostos majoritários - Santos, Tamiris Aparecida de Carvalho (2024)
Chemical control is commonly employed for managing agricultural diseases; however, issues such as environmental contamination and human health risks have prompted the search for new alternatives. Plant secondary metabolites (SMs) exhibit various biological activities, including microorganism control. Chalcones are produced in plant secondary metabolism but can also be obtained via the Claisen-Schmidt reaction. Other important SMs include essential oils (EOs), complex volatile mixtures with hydrophobic and odorous characteristics. Monoterpenes are constituents of various EOs, with thymol and carvacrol being the principal components in the EOs of the Lippia gracilis species. These monoterpenes demonstrate diverse biological activities, including antimicrobial effects. The objective of this study was to assess the antimicrobial potential of 15 chalcones against the fungi Macrophomina phaseolina, Sclerotium sp, Colletotrichum gloeosporioides, the bacterium Acidovorax citrulli, and the phytoparasite Phytomonas serpens. Additionally, the antimicrobial activity of EOs from seven Lippia gracilis accessions and the major compounds thymol and carvacrol were determined. Chalcones were initially screened for antifungal (1mM), antibacterial (1mM), and antiprotozoal (25µM) activities. Subsequently, molecules exhibiting inhibition above 50% were subjected to IC50 determination. For the fungus C. gloeosporioides, the molecule with the lowest IC50 was evaluated for its effect on fungal hyphal membrane permeability. MIC and MBC determination were conducted for the antimicrobial activity of the seven EOs, thymol, and carvacrol. A bacterial inoculum grown in LB medium at OD 0.5 was exposed to EOs and monoterpenes and incubated for 24 hours (150 rpm/28°C). Growth, antibiofilm activity, membrane permeability, and bacterial motility were evaluated. All data were expressed as mean and standard error; IC50 was calculated using a logarithmic equation, and the data were analyzed using analysis of variance and Dunnett's test with GraphPad Prism 8.1 software. Chalcones CH0, CH1, CH2, and CH8 exhibited the highest antifungal potential. The lowest observed IC50 was CH0 (47.3µM) against C. gloeosporioides. Treatment with CH0 resulted in increased permeability of C. gloeosporioides hyphal membranes. Evaluated chalcones reduced the viability of P. serpens by approximately 90%, with the most active being CH2, CH3, CH5, and CH14. All evaluated EOs inhibited the growth of A. citrulli (above 97.3%). The lowest MICs were OE 106 (500 µg/mL), thymol, and carvacrol (250µg/mL). Treatment with OE 106, thymol, and carvacrol at MIC inhibited bacterial growth after 30 minutes of exposure. With thymol also inhibiting growth at sub-inhibitory concentrations (½ MIC) after 60 minutes of exposure. Thymol exhibited superior antibiofilm activity, inhibiting 100% of biofilms at MIC. Increased membrane permeability was observed after 5 minutes of exposure to the MIC concentration of all three studied molecules. Swimming motility was significantly reduced with ½ and MIC concentrations of thymol and carvacrol. Chalcones, as well as the essential oils of Lippia gracilis and their major compounds, demonstrate antimicrobial potential for agricultural disease control.